2013
DOI: 10.1007/s10815-013-9973-5
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of anti-mullerian hormone on embryo quality, blastocyst development, and pregnancy rate following in vitro fertilization-embryo transfer (IVF-ET)

Abstract: Purpose The objective of this study was to investigate the predictive value of anti-Mullerian hormone (AMH) on fertilization rate (FR), blastocyst development, embryo quality, the outcome of the pregnancy and the live birth rate (LBR) following in vitro fertilization-embryo transfer (IVF-ET) /intracytoplasmic sperm injection (ICSI). Method In this prospective study outcomes were followed in 83 women undergoing cycles of IVF/ICSI within a university hospital. Basal serum AMH, follicle stimulating hormone (FSH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 33 publications
1
32
1
7
Order By: Relevance
“…In our study, young women with reduced ovarian reserve had a 23% decrease in pregnancy rates compared with young women with normal ovarian reserve. Similar studies have shown an association between reduced ovarian reserve and reduced pregnancy rates (Hazout et al 2004;Lekamge et al 2007;Wunder et al 2008;Brodin et al 2013;Hattori et al 2013;Honnma et al 2013;Li et al 2013;Lin et al 2013). Perturbations in post-translational modifications of proteins by SIRT5 may be contributing to the decline in oocyte viability that is seen in women with reduced ovarian reserve or women of advanced maternal age by altering key metabolic pathways.…”
Section: Discussionmentioning
confidence: 71%
“…In our study, young women with reduced ovarian reserve had a 23% decrease in pregnancy rates compared with young women with normal ovarian reserve. Similar studies have shown an association between reduced ovarian reserve and reduced pregnancy rates (Hazout et al 2004;Lekamge et al 2007;Wunder et al 2008;Brodin et al 2013;Hattori et al 2013;Honnma et al 2013;Li et al 2013;Lin et al 2013). Perturbations in post-translational modifications of proteins by SIRT5 may be contributing to the decline in oocyte viability that is seen in women with reduced ovarian reserve or women of advanced maternal age by altering key metabolic pathways.…”
Section: Discussionmentioning
confidence: 71%
“…A recent prospective study in nearly 900 women undergoing 1230 IVF cycles confirmed these findings, reporting that AMH level is strongly associated with both pregnancy and live birth rates, independent of age and oocyte yield (Brodin et al, 2013). However, other studies have not shown an association between AMH level and pregnancy rates or live births (Kedem et al, 2013;Lin et al, 2013;Mutlu et al, 2013;Reichman et al, 2014), including two separate metaanalyses (Broer et al, 2013;Iliodromiti et al, 2014b). A third meta-analysis found a weak association between AMH level and implantation and clinical pregnancy rates (Tal et al, 2015).…”
Section: Amh: the Evidence As A Predictive Methodsmentioning
confidence: 89%
“…Due to the specific population of breast cancer patients and their goal of fertility preservation in that study, embryo cryopreservation was a freeze-all condition performed at the pronuclear stage. Several studies have examined whether AMH levels are associated with successful supernumerary embryo cryopreservation, with some data showing a statistically significant correlation (16)(17)(18) and other data showing no difference (25). The cryopreservation of supernumerary embryos in the aforementioned studies was performed on day 3.…”
Section: Discussionmentioning
confidence: 99%